One-pot synthesis of human metabolites of SAR548304 by fungal peroxygenases. Issue 15 (1st August 2015) - Kiebist, Jan; Holla, Wolfgang; Heidrich, Johannes; Poraj-Kobielska, Marzena; Sandvoss, Martin; Simonis, Reiner; Gröbe, Glenn; Atzrodt, Jens; Hofrichter, Martin; Scheibner, Katrin
Graphical abstract: Abstract: Unspecific peroxygenases (UPOs, EC 1.11.2.1) have proved to be stable oxygen-transferring biocatalysts for H2 O2 -dependent transformation of pharmaceuticals. We have applied UPOs in a drug development program and consider the enzymatic approach in parallel to a conventional chemical synthesis of the human metabolites of the bile acid reabsorption inhibitor SAR548304. Chemical preparation of N, N -di-desmethyl metabolite was realized by a seven-step synthesis starting from a late precursor of SAR548304 and included among others palladium catalysis and laborious chromatographic purification with an overall yield of 27%. The enzymatic approach revealed that the UPO of Marasmius rotula is particularly suitable for selective N -dealkylation of the drug and enabled us to prepare both human metabolites via one-pot conversion with an overall yield of 66% N, N -di-desmethyl metabolite and 49% of N -mono-desmethylated compound in two separated kinetic-controlled reactions.